Ukraine’s Europeanization of Public Administration and Harmonizing Customs Legislation – Exploring a Pluralistic Approach - Кормич, Анатолій Іванович; Кормич, А. І.; Kormych, Anatolii I.; Завальнюк, Володимир Васильович; Завальнюк, В. В.; Zavalniuk, Volodymyr V.; Тодощак, Олег Володимирович; Тодощак, О. В.; Todoshchak, Oleh V.; Ульянов, Олексій Іванович; Ульянов, О. І.; Ulianov, Oleksii I. (Odesa : Publishing House Helvetica, 2024)
The article examines the application of the concept of legal pluralism to the interaction between the European Union (EU) administrative legal order and the administrative legal orders of associated or candidate States as part of the process of aligning national legislation with EU standards. This process involves multiple sources of integration obligations derived from the Association Agreement, accession negotiations, conditions for economic aid, administrative cooperation, and EU-funded modernization programs. The authors suggest that a pluralistic approach may provide associated or candidate States with a degree of flexibility in choosing specific scopes, models, and time frames to align their national legislation with EU laws. This can help to mitigate and offset the imbalance in States’ relations with the EU resulting from the latter’s normative dominance. At the same time, various sources can lead to conflicts between integration obligations and approaches to harmonizing national administrative rules and practices.
Kormych A. Ukraine’s Europeanization of Public Administration and Harmonizing Customs Legislation – Exploring a Pluralistic Approach / A. Kormych, V. Zavalniuk, O. Todoshchak et al. // Lex Portus. – Odesa : Publishing House Helvetica, 2024. – 10(4). - P. 20-30. URL: https://doi.org/10.62821/lp10402
Keywords: legal pluralism; public administration; European integration; political arrangements; administrative law; customs law; Ukraine